2018
DOI: 10.1080/09712119.2018.1555091
|View full text |Cite
|
Sign up to set email alerts
|

Is the use of supermarket trolleys microbiologically safe? Study of microbiological contamination

Abstract: Microbial contamination in shopping trolleys (eighty five) by considering different supermarkets (seven) from three major food companies in Las Palmas de Gran Canaria (Spain) was determined. The two sampled areas were trolley handles and food trolley baskets-child seats. Samples were analyzed by selective and differential microbiological culture media. E. coli four (2.4%) indicative of faecal contamination, Klebsiella pneumoniae twelve (6.5%) and Citrobacter freundii, six (5.1%), which have been isolated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
(60 reference statements)
1
4
3
Order By: Relevance
“…The rate of shopping trolley and basket contamination was 28%. The presence of bacterial isolates in this study was lower than the results obtained in Jeddah by Al-Ghamdi et al [16], in the USA by Gerba and Maxwell [20], in Saudi Arabia by Ashgar and El-Said [21] and in Spain by Carrascosa et al [11], who reported the contamination rate as 95.5%, 72%, 48% and 35% respectively. The reduced prevalence obtained in our study could be due to the small sample size and availability of resources.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The rate of shopping trolley and basket contamination was 28%. The presence of bacterial isolates in this study was lower than the results obtained in Jeddah by Al-Ghamdi et al [16], in the USA by Gerba and Maxwell [20], in Saudi Arabia by Ashgar and El-Said [21] and in Spain by Carrascosa et al [11], who reported the contamination rate as 95.5%, 72%, 48% and 35% respectively. The reduced prevalence obtained in our study could be due to the small sample size and availability of resources.…”
Section: Discussioncontrasting
confidence: 77%
“…Individuals also visit shopping malls with different health states. Someone infected may not be aware that they are carriers and may unknowingly contribute to spreading pathogenic bacteria in public areas [11]. Accidental contamination might also occur with raw food products such as meat, fish and chicken contact directly [12].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of association in our study may reflect that this practice is not common in Hong Kong. Shopping carts are frequently handled by numerous users and not routinely disinfected in supermarkets 37 and have high microbiological loads on handles and basket-child seats. Children may come into direct contact with Salmonella through touching contaminated packaging of raw chicken meat contaminated with Salmonella 38 39 suggesting that parents should prevent their child touching raw products and use hand sanitizer to wipe shopping carts.…”
Section: Discussionmentioning
confidence: 99%
“…These isolates were characterized as non‐MDRs but had different biofilm formation capacities and belonged to different STs as well. Many studies have investigated the contamination of shopping cart handles with pathogenic bacteria and coliforms (Al‐Ghamdi et al, 2011; Mizumachi et al, 2011; Gerba & Maxwell, 2012; Fawzi I. Fawzi et al, 2014; Carrascosa et al, 2019; Calle et al, 2020; Jaradat et al, 2021), but none of them described the isolation of A. baumannii from these surfaces. These handles are considered as high touch surfaces, and thus contribute to the spread of pathogens among shoppers and in the community.…”
Section: Discussionmentioning
confidence: 99%